2016
DOI: 10.1002/1873-3468.12366
|View full text |Cite
|
Sign up to set email alerts
|

Conserved functions of human Pelota in mRNA quality control of nonstop mRNA

Abstract: Dom34-Hbs1 plays crucial roles in Nonstop Decay (NSD) and No-Go Decay (NGD). Here, we report a conserved function of human Pelota (hPelota) in mRNA quality control of nonstop mRNA. hPelota facilitated the expression of the nonstop products from GFP-Rz mRNA, which lacks a termination codon and a poly(A) tail, in exosome-defective mutant cells. hPelota promoted the dissociation of stalled ribosomes at the 3' end of GFP-Rz mRNA, and mutations in domain A diminished this activity. The hPelota-R45A mutant associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Cells must therefore identify defective rounds of translation and take action before the nascent chain leaves the ribosome (Brandman and Hegde 2016). Degradation of the products of stalled translation is conserved throughout Eukarya (Passos et al 2009;Shao et al 2013Shao et al , 2015Shao and Hegde 2014;Ikeuchi et al 2016), and failures in this response have been linked to dysregulation of protein homeostasis (Choe et al 2016;Defenouillere et al 2016;Yang et al 2016;Yonashiro et al 2016) and neurodegenerative phenotypes (Chu et al 2009;Ishimura et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Cells must therefore identify defective rounds of translation and take action before the nascent chain leaves the ribosome (Brandman and Hegde 2016). Degradation of the products of stalled translation is conserved throughout Eukarya (Passos et al 2009;Shao et al 2013Shao et al , 2015Shao and Hegde 2014;Ikeuchi et al 2016), and failures in this response have been linked to dysregulation of protein homeostasis (Choe et al 2016;Defenouillere et al 2016;Yang et al 2016;Yonashiro et al 2016) and neurodegenerative phenotypes (Chu et al 2009;Ishimura et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies structurally associated Hbs1 with eRF3 and eEF1A [13], and recognition of Dom34 as an Hbs1-interacting protein functionally linked the complex to translation [14]. Recent biochemical studies have shown that Dom34:Hbs1 promotes the dissociation of the stalled ribosome into subunits [8, 15, 16] during aberrant translation. Subunit dissociation is a critical component of canonical ribosomal recycling, a process to reutilize ribosomes from a terminated or aberrant round of translation.…”
Section: Introductionmentioning
confidence: 99%
“…X420Y mutation in MITF introduces 99 nucleotide acids before the alternative in-frame stop codon; it is likely to trigger nonstop mRNA decay. 32, 33 …”
Section: Discussionmentioning
confidence: 99%